Sinkronisasi Pasal 1868 KUH Perdata Dalam Menunjang Terselenggaranya Konsep Cyber Notary di Indonesia - Putra Arya; Aju Putrijanti; Mujiono Hafidh Prasetyo (Magister Kenotariatan Universitas Diponegoro, 2021)
he implementation of cyber notary in Indonesia raises legal phenomena. On the one hand, cyber notary enhances the capabilities of Notaries in accordance with current technological developments. On the other hand, cyber notary creates an unsynchronization between traditional Notary tasks and digital Notary tasks. The purpose of writing is to synchronize the implementation of the tasks of the Notary according to the Law and the Civil Code, and the implementation of the tasks of the Notary according to the ITE Law. The results of the study and the conclusion that the application of cyber notary in Indonesia raises doubts for the Notary regarding the saving of the minutes of the deed, must be stored manually or electronically, in line with the lack of legal basis governing the mechanism for the storage of the minutes of the deed. The conclusion is cyber notary in Indonesia should not be fully implemented and there needs to be some consideration because the legal system in Indonesia with the legal system in other countries is much different.Keywords : Synchronization of Article 1868 Civil Code; cyber notaryAbstrakImplementasi cyber notary di Indonesia menimbulkan fenomena hukum. Di satu sisi, cyber notary meningkatkan kemampuan Notaris sesuai perkembangan teknologi saat ini. Di sisi lain, cyber notary menimbulkan ketidaksinkronan antara pelaksanaan tugas Notaris secara tradisional dengan pelaksanaan tugas Notaris era digital. Tujuan penulisan ingin mensinkronisasikan antara pelaksanaan tugas Notaris sesuai UUJN dan KUHPerdata, dengan pelaksanaan tugas Notaris sesuai Undang-Undang ITE. Hasil penelitian dan kesimpulan bahwa penerapan cyber notary di Indonesia menimbulkan keragu-raguan bagi Notaris terkait penyimpanan minuta akta, harus disimpan secara manual atau elektronik, sejalan belum adanya dasar hukum yang mengatur mekanisme penyimpanan minuta akta. Simpulannya adalah cyber notary di Indonesia sebaiknya tidak sepenuhnya diterapkan dan perlu adanya beberapa pertimbangan karena sistem hukum di Indonesia dengan sistem hukum di negara lain jauh berbeda.Kata kunci : Sinkronisasi Pasal 1868 KUHPerdata; cyber notary